Implementasi Sistem Informasi Desa Dan Kependudukan Berbasis Website Menggunakan Metode Prototype - Ramadhan, M Abdulhafiizh; Oktaviani, Nia (Journal of Information System Research (JOSH), 2025)
The advancement of information technology has a significant impact on various aspects of life, including village administration services. Jejawi Village, Ogan Komering Ilir Regency, still faces obstacles in managing population data, correspondence, business permits, and asset management which are still done manually. This causes various problems, such as service delays, recording errors, and difficulties in storing and processing data. This study aims to design and build a website-based village information system to improve the efficiency and effectiveness of public services in Jejawi Village. The method used in developing this system is the Prototype method, which allows testing and gradual system improvement according to user needs. The technology used in developing the system includes PHP as a programming language, MySQL as a database management system, and XAMPP as a local server. The development of this system was carried out without using a special framework such as Laravel or CodeIgniter, but rather based on native PHP. The results of this study are a website-based information system that facilitates access to village administration services for the community and village officials. With this system, the process of making letters, managing assets, and recording population data becomes faster, more transparent, and more accurate. The implementation of this system is expected to improve the quality of public services in Jejawi Village and become a reference in the development of other village information systems.